Meningkatkan Hasil Belajar PAK dengan Menggunakan Model PBL pada Kelas VII SMP Negeri 1 Belimbing - Yohana Leonisa Tukan (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research is motivated by the lack of maximum student learning outcomes in Catholic Religious Education subjects in Class VII SMP Negeri 1 Belimbing. Efforts to improve learning outcomes in Catholic Religious Education are continuously developed by the government and schools through curriculum improvement. This Problem Based Learning (PBL) learning model is designed with stages of solving problems, students will explore the concepts they must master themselves, and students are activated to ask questions and argue through discussions, hone investigative skills, and undergo other scientific work procedures. The purpose of this research is designed to develop effective learning strategies and determine the learning outcomes of students in Catholic Religious Education subjects with the Problem Based Learning (PBL) learning model. The mode of this research is Classroom Action Research (PTK) conducted in two cycles. Each cycle consists of one meeting and four stages, namely planning, implementation, observation, and reflection. The research subjects consisted of 12 students of class VIIA SMP Negeri 1 Belimbing. Data collection techniques were in the form of tests and observations. Data analysis and processing techniques are carried out periodically at the end of each cycle, the technique used in data analysis is descriptive qualitative. The success indicators in this study can be seen from the abilities and activities of students while learning by using the PBL model from the achievement of students' scores at the end of the cycle with indicators of proficient = 40%, capable = 50%, feasible = 10% and newly developing = 0% students are also expected to be able to reach the target with a score of 48 on each indicator of a sense of responsibility. The results of this study can be concluded that the results in cycle one there were 3 students in the advanced category with a percentage of 25% increased, in the second cycle there were 5 people who were in the advanced category with a percentage of 42%. Thus it can be concluded that using the Problem Based Learning (PBL) method can improve the learning outcomes of Catholic Religious Education class VII students at SMP Negeri 1 Belimbing.